Efektifitas Pendidikan Kesehatan Seksual Dalam Meningkatkan Literasi Kesehatan Reproduksi dan Sikap Preventif Remaja - Rifdha Wahyuni; Marisa Anggraini; Ratna Dewi (Journal of Pharmaceutical and Sciences, 2026)
Adolescence is a developmental period characterized by physical, psychological, and social changes that increase vulnerability to risky sexual behaviors. Low reproductive health literacy and inadequate preventive attitudes among adolescents may contribute to various health problems, including unintended pregnancy and sexually transmitted infections. This study aimed to determine the effectiveness of sexual health education in improving reproductive health literacy and preventive attitudes among adolescents at SMP Negeri 32 Padang in 2026. This study employed a quasi-experimental design with a one-group pretest-posttest approach. The population consisted of 188 eighth-grade students, and 20 respondents were selected using a systematic random sampling technique. Data were collected using knowledge and attitude questionnaires administered before and after the sexual health education intervention and were analyzed using the Wilcoxon test. The results showed that the mean score of reproductive health literacy increased from 12.55 to 14.15, while the mean score of preventive attitudes increased from 8.10 to 9.65. Statistical analysis revealed significant improvements in reproductive health literacy (p=0.000) and preventive attitudes (p=0.000) following the intervention. In conclusion, sexual health education is effective in improving adolescents’ reproductive health literacy and preventive attitudes and can serve as a promotive and preventive strategy to support adolescent reproductive health in the school setting.